Rapid selection of genetic and antigenic variants of foot-and-mouth disease virus during persistence in cattle. - Gebauer, F (1988)
Rapid evolution of foot-and-mouth disease virus (FMDV) is documented during persistent infections of cattle. The carrier state was established experimentally with plaque-purified FMDV of serotype C3. Virus was recovered from the esophageal pharyngeal area of the animals up to 539 days postinfection. Analysis of capsid proteins by electrofocusing and by electrophoretic mobility of the genomic poly(C)-rich tract suggested heterogeneity in several isolates and sequential dominance of viral subpopulations. Nucleotide sequences of the VP1-coding region of the parental FMDV C3 clones and of seven isolates from the carrier cattle showed point mutations that represented rates of fixation of mutations of 0.9 X 10(-2) to 7.4 X 10(-2) substitutions per nucleotide per year; 59% of the base changes led to amino acid substitutions, some of which were located within residues 135 to 151, a region involved in neutralization of FMDV. In the esophageal pharyngeal fluid samples, FMDV C3-neutralizing activity was present. Antigenic variation was demonstrated with monoclonal antibodies raised against FMDV C3. Two isolates from carrier cattle differed from the parental virus by 10(2)- or 10(3)-fold decreased reactivity with neutralizing monoclonal antibodies. We suggest that persistent, inapparent infections of ruminants, in addition to being a reservoir of virus, may promote the rapid selection of antigenically variant FMDVs.